2003
DOI: 10.1128/jb.185.15.4315-4325.2003
|View full text |Cite
|
Sign up to set email alerts
|

PlmA, a New Member of the GntR Family, Has Plasmid Maintenance Functions in Anabaena sp. Strain PCC 7120

Abstract: The filamentous cyanobacterium Anabaena (Nostoc) sp. strain PCC 7120 maintains a genome that is divided into a 6.4-Mb chromosome, three large plasmids of more that 100 kb, two medium-sized plasmids of 55 and 40 kb, and a 5.5-kb plasmid. Plasmid copy number can be dynamic in some cyanobacterial species, and the genes that regulate this process have not been characterized. Here we show that mutations in an open reading frame, all1076, reduce the numbers of copies per chromosome of several plasmids. In a mutant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 54 publications
(35 reference statements)
0
68
0
Order By: Relevance
“…For all constructs, the ribosome-binding site and start codon were derived from the promoters used. In all constructs, the inserts were downstream of a transcription terminator on shuttle vectors pAM504, pAM505, and pAM2770 (23,32,36). All plasmid constructs were confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all constructs, the ribosome-binding site and start codon were derived from the promoters used. In all constructs, the inserts were downstream of a transcription terminator on shuttle vectors pAM504, pAM505, and pAM2770 (23,32,36). All plasmid constructs were confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of full-length patS and the patS5 minigene from the rbcL promoter in constructs P rbcL -patS17 (pAM1690) (23) and P rbcL -patS5 (pAM2537) completely inhibited heterocyst formation in both the wild-type strain and the patS null mutant AMC451 (Table 4). P rbcL is strongly expressed in vegetative cells (7,9).…”
Section: Expression Of the Pats5 Minigene In Proheterocysts Failed Tomentioning
confidence: 99%
See 1 more Smart Citation
“…To date, in addition to AraR, 21 proteins presenting this mosaic modular association in different bacteria have been sequenced. Together they constitute one of the six GntR subfamilies typified by AraR (17,38). However, no functional studies have been reported for these AraR-like proteins (http://www.sanger.ac.uk /Software/Pfam).…”
mentioning
confidence: 99%
“…The BamHIEcoRI fragment containing the p petE -kgtP fusion was subcloned into the shuttle vector pRL25c. pRL25c, like pAM1691, is a derivative of pDU1; the copy number of pAM1691 is about 17 per chromosome (Lee et al, 2003). The construct was conjugated into Anabaena sp.…”
Section: Methodsmentioning
confidence: 99%